Gene expression of nuclear factor of activated T-cells in children with bicuspid aortic valve - Kamenshchyk А.V.; Kamyshny A.М.; Ivanko О.G. (Medičnì Perspektivi)
The genes of nuclear factor of activated T-cells (NFATC) play a key role both in heart valves formation and immune response. The genes belong to transcriptional factors and lead to myocardial hypertrophy in postnatal period that is confirmed by experimental models on animals. The purpose of this study was to reveale NFATC1 and NFATC4 genes expression level in the blood of 30 children with congenital heart diseases (CHD), 15 of them had bicuspid aortic valve, 15 had CHD without valve anomalies and 15 healthy children of the control group. No patients had signs of heart failure. At the first sage of Doppler heart ultrasound study a significant increase of the left ventricle posterior wall and ventricular septum thickness in comparison with CHD and control was revealed in BAV group. At the second stage a significant rise of relative normalized expression of NFATC1 in BAV children compared to CHD and control without differences in the expression of NFATC4 gene were established. Thus, in children with bicuspid aortic valve, formation of early myocardial hypertrophy with changes in nuclear factor of activated T-cells genes expression with prevailing of NFATC1 expression takes place. The detection of NFATC1 expression level in the blood of children could be considered as an early marker of progressive myocardial hypertrophy.